Understanding the delayed Amundsen Sea low response to ENSO - Lee, Hyun-Ju; Jin, Emilia Kyung (Frontiers in Earth Science, 2023)
Although the El Niño-Southern Oscillation (ENSO) affects West Antarctica via teleconnection, it is delayed by a season, because the Amundsen Sea Low (ASL) anomaly in response to the ENSO is the strongest in May. However, the process and mechanism of the delay has not been fully elucidated yet. In this study, we examined the formation of the ENSO-driven teleconnection in each month from January to May by analyzing the kinetic energy conversion and Rossby wave propagation. The flow perturbed by the ENSO gains energy from the basic state by energy conversion, but the perturbation does not reach the high latitudes until April. In May, although the ENSO intensity becomes weak, the development of the subtropical jet induces waves to propagate further south, resulting in the anticyclonic circulation anomaly over the ASL region. Numerical experiments that account for the decay of the ENSO forcing and the monthly varying basic state also indicate that the formation of the teleconnection is the strongest in May. The results reveal that the configuration of the basic state is crucial for the teleconnection in response to the ENSO to reach West Antarctica.